Charting the path along the continuum of PMCT or HIV-1 to elimination and finally to eradication - Ramkissoon, A; Coovadia, H (My University, 2014)
In this editorial we traverse the continuum of transmission of HIV-1 from mothers to children to highlight the biomedical history of this problem. Treatment has progressed from prevention with antiretrovirals (ARVs) through to a broader set of interventions, including various breastfeeding options and other health system improvements, that have increased the possibility of eliminating mother-to-child-transmission (MTCT) of HIV.
KM
Keywords: Acquired Immunodeficiency Syndrome; Infectious Disease Transmission, Vertical; HIV-1